Объяснение:
[tex]sin70^0-cos40^0=sin70^0-sin(90^0-40)=sin70^0-sin50^0=\\=2*sin\frac{70^0-50^0}{2}*cos\frac{70^0+50^0}{2}=2*sin10^0*cos60^0=2*sin10^0*\frac{1}{2}=sin10^0.[/tex]
Ответ:
sin70
0
−cos40
=sin70
−sin(90
−40)=sin70
−sin50
=
=2∗sin
2
70
−50
∗cos
+50
=2∗sin10
∗cos60
∗
1
=sin10
.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Объяснение:
[tex]sin70^0-cos40^0=sin70^0-sin(90^0-40)=sin70^0-sin50^0=\\=2*sin\frac{70^0-50^0}{2}*cos\frac{70^0+50^0}{2}=2*sin10^0*cos60^0=2*sin10^0*\frac{1}{2}=sin10^0.[/tex]
Ответ:
sin70
0
−cos40
0
=sin70
0
−sin(90
0
−40)=sin70
0
−sin50
0
=
=2∗sin
2
70
0
−50
0
∗cos
2
70
0
+50
0
=2∗sin10
0
∗cos60
0
=2∗sin10
0
∗
2
1
=sin10
0
.